Transcriptome and Proteomics Analysis of Wheat Seedling Roots Reveals That Increasing NH4+/NO3– Ratio Induced Root Lignification and Reduced Nitrogen Utilization - Yang, Dongqing; Zhao, Jihao; Bi, Chen; Li, Liuyin; Wang, Zhenlin (Frontiers in Plant Science, 2022)
Wheat growth and nitrogen uptake gradually decrease in response to high NH4+/NO3- ratio. However, the mechanisms underlying the response of wheat seedling roots to changes in NH4+/NO3- ratio remain unclear. In this study, we investigated wheat growth, transcriptome, and proteome profiles of roots in response to increasing NH4+/NO3- ratios (Na:100/0; Nr1: 75/25, Nr2: 50/50, Nr3: 25/75, Nn: 0/100). High NH4+/NO3- ratio significantly reduced leaf relative chlorophyll content, Fv/Fm, and ΦII values. Both total root length and specific root length decreased with increasing NH4+/NO3- ratios. Moreover, the rise in NH4+/NO3- ratio significantly promoted O2- production. Furthermore, transcriptome sequencing and tandem mass tag-based quantitative proteome analyses identified 14376 differentially expressed genes (DEGs) and 1819 differentially expressed proteins (DEPs). KEGG pathway enrichment analysis indicated that glutathione metabolism and phenylpropanoid biosynthesis were the main two shared enriched pathways across ratios comparisons. Up-regulated DEGs and DEPs involving glutathione S-transferases may contribute to the prevention of oxidative stress. An increment in the NH4+/NO3- ratio induced the expression of genes and proteins involved in lignin biosynthesis, which increased root lignin content. Additionally, phylogenetic tree analysis showed that both A0A3B6NPP6 and A0A3B6LM09 belong to the cinnamyl-alcohol dehydrogenase subfamily. Fifteen down-regulated DEGs were identified as high-affinity nitrate transporters or nitrate transporters. Up-regulated TraesCS3D02G344800 and TraesCS3A02G350800 were involved in ammonium transport. Down-regulated A0A3B6Q9B3 is involved in nitrate transport, while A0A3B6PQS3 is a ferredoxin-nitrite reductase. This may explain why an increase in the NH4+/NO3- ratio significantly reduced root NO3--N content but increased NH4+-N content. Overall, these results demonstrated that increasing the NH4+/NO3- ratio at the seedling stage induced the accumulation of reactive oxygen species, which in turn enhanced root glutathione metabolism and lignification, thereby resulting in increased root oxidative tolerance at the cost of reducing nitrate transport and utilization, which reduced leaf photosynthetic capacity and, ultimately, plant biomass accumulation.